Multilevel Analysis: Factors Related to Work Performance in Health Workers at Community Health Centers - Widiantoro, Reza; Tamtomo, Didik Gunawan; Rahardjo, Setyo Sri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Patient satisfaction is a very valuable asset because if patients are satisfied they will continue to use the services of their choice. The level of patient satisfaction arises as a result of the performance of health services obtained after the patient compares it with the quality of health services. The aim of this research is to analyze the performance of health workers at community health centers. Subjects and Method: Cross-sectional research was conducted at community health centers in Karanganyar, Central Java, from November to December 2023. A total of 210 health workers were selected using stratified random sampling. The dependent variable was work performance. The independent variables were age, length of work, employment status, income and work environment. Data were collected using questionnaires and analyzed using multiple multilevel linear regression. Results: Age decreased the performance but was not statistically significant (b= -0.33; CI 95%= -1.63 to 0.97; p = 0.623). Length of work (b= -1.19; CI 95%= -2.30 to -0.08; p= 0.035) and income (b= -1.43; CI 95%= -2.78 to -0.07; p = 0.039) significantly degraded the performance. Employment status decreased performance but it was statistically close to significant (b= -1.44; CI 95%= -3.04 to 0.16; p = 0.078). A comfortable work environment significantly increased performance (b= 0.16; 95% CI= 0.02 to 0.30; p = 0.029). There was a contextual influence of community health center factors on work performance (ICC= 9.62%). Conclusion: Age decreases performance but is not statistically significant. Length of work and income significantly decrease performance. Employment status decreases performance but is statistically close to significant. A comfortable work environment significantly improves performance. There is a contextual effect of community health center factors on work performance.